2019
DOI: 10.1037/dev0000663
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatics and spatial language: The acquisition of front and back.

Abstract: Across languages, children produce locative back earlier and more frequently than front, but the reasons for this asymmetry are unclear. On a semantic misanalysis explanation, early meanings for front and back are nonadult (nongeometric), and rely on notions of visibility and occlusion respectively. On an alternative, pragmatic inference explanation, visibility and occlusion are simply pragmatic aspects of the meaning of front and back; the profile of back can be explained by the fact that occlusion is more no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…Our study has shown that the spatial relation terms selected in given spatial situations (the same locatum-relatum pair) are not always those predicted by standard translations of spatial relation terms between the two languages, and that often a range of different spatial relation terms are used for a scene that predominantly uses one spatial relation term in the other language. These results were contrary to studies with other romance languages that have shown notable similarities with English , but a number of studies focusing on specific spatial relation terms or groups thereof have confirmed that many cross-linguistic mappings between spatial relation terms are complex (Chuang, 2017;Coventry, Valdés, Castillo, & Guijarro-Fuentes, 2008;Grigoroglou, Johanson, & Papafragou, 2019;Vandeloise, 2017). Most of these studies have focused on particular pairs or groups of terms that are known to be similar, and studied their subtle variations, in contrast to our data-driven approach which enables us to highlight relationships between pairs of terms that would not normally be considered similar, as in Figure 8.…”
Section: Spatial Relation Term Mappingscontrasting
confidence: 96%
“…Our study has shown that the spatial relation terms selected in given spatial situations (the same locatum-relatum pair) are not always those predicted by standard translations of spatial relation terms between the two languages, and that often a range of different spatial relation terms are used for a scene that predominantly uses one spatial relation term in the other language. These results were contrary to studies with other romance languages that have shown notable similarities with English , but a number of studies focusing on specific spatial relation terms or groups thereof have confirmed that many cross-linguistic mappings between spatial relation terms are complex (Chuang, 2017;Coventry, Valdés, Castillo, & Guijarro-Fuentes, 2008;Grigoroglou, Johanson, & Papafragou, 2019;Vandeloise, 2017). Most of these studies have focused on particular pairs or groups of terms that are known to be similar, and studied their subtle variations, in contrast to our data-driven approach which enables us to highlight relationships between pairs of terms that would not normally be considered similar, as in Figure 8.…”
Section: Spatial Relation Term Mappingscontrasting
confidence: 96%
“…Nevertheless, the case of Front-Behind can be distinguished by notions of visibility (in the case of Front) and occlusion (in the case of Behind). These notions provide an asymmetrical relationship between Front and Behind (see Grigoroglou et al, 2019 for a discussion). Therefore, Front can be distinguished from Behind.…”
Section: Locative Spatial Relations: a Domain To Study The Developmen...mentioning
confidence: 99%
“…For spoken languages, linguistic encoding of spatial terms has been found to follow a certain developmental order reflecting the cognitive complexity of the spatial relations reviewed above (1.1.1.). For instance, speaking children first acquire terms such as In-On-Under to refer to viewpoint-independent spatial relations between objects (e.g., Casasola, 2008;Casasola et al, 2003;Clark, 1973;Johnston & Slobin, 1979), followed by viewpoint-dependent relations such as Front-Behind (Durkin, 1980(Durkin, , 1981Grigoroglou et al, 2019;Johnston & Slobin, 1979;Piaget & Inhelder, 1971). Linguistic encoding of viewpoint-dependent Left-Right relations, however, appears later (Abarbanell & Li, 2021;Benton, 1959;Harris, 1972;Piaget, 1972;Rigal, 1994Rigal, , 1996Sümer, 2015).…”
Section: Cross-linguistic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the age of acquisition, some of these studies have explored the influence of reference frames on locative comprehension (Johnston and Slobin 1979;Cox 1981;Johnston 1984;Conner and Chapman 1985;Bialystok and Codd 1987;Cox and Isard 1990;Coventry, Prat-Sala, and Richards 2001;Grigoroglou, Johanson, and Papafragou 2019). These studies found that young children (e.g., two to three years old) responded to tasks from an egocentric or observer perspective and that this shifted with increasing age to the use of an intrinsic reference frame that was based on object features.…”
Section: Relevant Literature Locatives Tested In Previous Studiesmentioning
confidence: 99%